The interaction of the mitochondrial protein importer TOMM34 with HSP70 is regulated by TOMM34 phosphorylation and binding to 14-3-3 adaptors - Trcka, Filip; Durech, Michal; Vankova, Pavla; Vandova, Veronika; Simoncik, Oliver; Kavan, Daniel; Vojtesek, Borivoj; Muller, Petr; Man, Petr (The Journal of biological chemistry, 2020)
Translocase of outer mitochondrial membrane 34 (TOMM34) orchestrates heat shock protein 70 (HSP70)/HSP90-mediated transport of mitochondrial precursor proteins. Here, using in vitro phosphorylation and refolding assays, analytical size-exclusion chromatography, and hydrogen/deuterium exchange MS, we found that TOMM34 associates with 14-3-3 proteins after its phosphorylation by protein kinase A (PKA). PKA preferentially targeted two serine residues in TOMM34: Ser93 and Ser160, located in the tetratricopeptide repeat 1 (TPR1) domain and the interdomain linker, respectively. Both of these residues were necessary for efficient 14-3-3 protein binding. We determined that phosphorylation-induced structural changes in TOMM34 are further augmented by binding to 14-3-3, leading to destabilization of TOMM34's secondary structure. We also observed that this interaction with 14-3-3 occludes the TOMM34 interaction interface with ATP-bound HSP70 dimers, which leaves them intact and thereby eliminates an inhibitory effect of TOMM34 on HSP70-mediated refolding in vitro In contrast, we noted that TOMM34 in complex with 14-3-3 could bind HSP90. Both TOMM34 and 14-3-3 participated in cytosolic precursor protein transport mediated by the coordinated activities of HSP70 and HSP90. Our results provide important insights into how PKA-mediated phosphorylation and 14-3-3 binding regulate the availability of TOMM34 for its interaction with HSP70.
Keywords: MCF-7 Cells; hydrogen-deuterium exchange; signální transdukce; DNA-Binding Proteins; protein folding; phosphorylation; Protein Binding; molekulární chaperony; 14-3-3 Proteins; Phosphorylation; Mitochondrial Membrane Transport Proteins; 14-3-3 protein; HSP70 Heat-Shock Proteins; Signal Transduction; 70-kDa heat shock protein (Hsp70); protein import; HSP72 Heat-Shock Proteins; Transcription Factors; Hsp70; Tomm34; protein–protein interaction; MFC-7 buňky; proteiny tepelného šoku HSP90; mitochondriální importní komplex; Mitochondrial Proteins; transkripční faktory; HSP70; Humans; Cyclic AMP-Dependent Protein Kinases; mitochondriální membrány; translocase of outer mitochondrial membrane 34 (TOMM34); vazba proteinů; protein kinase A (PKA); proteinkinasy závislé na cyklickém AMP; dimerization; DNA vazebné proteiny; fosforylace; molecular chaperone; proteiny tepelného šoku HSP72; protein-nucleic acid interaction; proteiny 14-3-3; proteiny tepelného šoku HSP70; transportní proteiny mitochondriální membrány; Mitochondrial Precursor Protein Import Complex Proteins; Molecular Chaperones; mitochondriální proteiny; Mitochondrial Membranes; lidé; HSP90 Heat-Shock Proteins